Liposomal drug products and recent advances in the synthesis of supercritical fluid-mediated liposomes. (September 2013) - Karn, Pankaj Ranjan; Cho, Wonkyung; Hwang, Sung-Joo
Since the pioneering research of Bangham et al. in 1965, liposomes have attracted a large amount of interest as potential carriers of various bioactive molecules for clinical applications. However, scaling-up conventional methods of liposome preparation has been proven to be challenging. Compared with conventional methods, processes that use supercritical fluid (SCF)-CO2 require a reduced amount of organic solvent, are relatively fast and simple to perform, and yield stable and more uniform liposomes. A number of studies have demonstrated that SCF-CO2 methods might be suitable for industrial-scale manufacturing of liposomes. In this review there are two topics being discussed. We provide an overview of liposomal drug products and aim to describe the physicochemical properties of liposomes prepared using various SCF methods. We review all of the available literature on SCF-CO2 -based liposomes and focus on the future applications of these innovative technologies in industrial-scale liposome preparation.